Recent Publications (Quarterly Journal of Economics, 1963)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 77, Issue 3, August 1963, Pages 515–516, https://doi.org/10.1093/qje/77.3.515 Published: 01 August 1963